PROKALSITONIN, CRP DAN PRESEPSIN SERUM DI SIRS - Hendrianingtyas Hendrianingtyas; Banundari RH; Indranila KS; Imam Budiwiyono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Infection in ICU patients can lead to a septic condition with clinical signs similar to Systemic Inflammatory Response Syndrome (SIRS). The high risk of death and high cost of sepsis is the reason to find an early marker in diagnosing sepsis. Blood culture can givea result in 1-3 days, so C reactive protein, procalcitonin and presepsin which are fast and accurate are needed to find a septic condition in SIRS patients. The aim of this study is to determine the diagnostic value of CRP, PCT and presepsin of sepsis with blood culture as the gold standard., The samples were collected from 32 clinically SIRS patients in the Dr. Kariadi Hosiptal, Semarang. The PCT level was measured using ELFA method, CRP level by PET IA method, while presepsin level by CLEA method. The determined area was under curve (AUC) and the cut off level was determined by 2×2 table to find out the sensitivity, spesificity, positive predictive value, negative predictive value and likelihood ratio of CRP, PCT and presepsin as well. The AUC of PCT, CRP and presepsin was 0.78 (cut off 4.314 ng/mL); 0.673 (cut off 10.245 mg/L) and 0.814 (cut off 1134.5 pg/mL). The presepsin level had a higher sensitivity (90%) than PCT (80%) and CRP (70%). PCT specificity was 72.73%, presepsin and CRP specificity each was 68.18%. Based on this study, AUC and sensitivity of presepsin level were found higher than the PCT and CRP level.